Diefenbaker's world : a populist in foreign affairs - Robinson, H. Basil (Henry Basil), 1919- (University of Toronto Press, 2018)
Politicking on the streets of Prince Albert, Saskatchewan, John Diefenbaker was in his element. He was much less at home negotiating with the heads of other governments and formulating foreign policy. As prime minister from 1957 to 1963, Diefenbaker oversaw Canada's role in some of the most dramatic moments of twentieth-century world affairs, but it was an arena in which The Chief was never really comfortable. The Diefenbaker years were a distinctive era in Canada's external affairs, both in the international challenges the country faced and in the style with which government met those challenges. Basil Robinson served Diefenbaker as External Affairs liaison officer for five years. He presents an informed, balanced, and clear-eyed assessment of the time and the man whose compelling personality shaped it. For Robinson and others who had worked in the department of External Affairs in its post-war glory days, the period of transition was difficult. They found Diefenbaker always interested, conscientious, and accessible to his immediate advisers. But each of his foreign policy decisions was inevitably coloured by domestic political considerations: how would it play in Saskatoon? That question informed Diefenbaker's' attitudes on most of the international issues that confronted him: the North American air defence agreement (NORAD); the controversy over the stationing of nuclear weapons on Canadian soil; the withdrawal of South Africa from the Commonwealth; his attempt to obstruct the United Kingdom's negotiation for entry into the European Economic Community; the crises of Berlin in 1961 and Cuba in 1962; and the nuclear weapons controversy which brought about the fall of his government in 1963. Robinson takes us through each of these developments and Diefenbaker's handling of them. We find out why he got along so well with Dwight D. Eisenhower and so badly with John F. Kennedy, and about the ups and downs of his relationship with Harold Macmillan. We get to know the advisers with whom he surrounded himself, and to understand why he chose them. We learn what made him anxious, what gave him confidence. And we see what impact all those things had on the way Canada interacted with our allies and enemies in those years of international tension.